Assessing the Effect of Apremilast on Serum Leptin levels in Obese Patients with Psoriasis - Saad, Haitham Mohammed; Noaimi, Adil A.; Mahmood, Halla G. (AL-Kindy College Medical Journal, 2024)
Background: Psoriasis is a common inflammatory condition worldwide, with an average prevalence ranging from 2% to 3%. However, the incidence of psoriasis varies among different ethnic groups and regions. Elevated leptin levels have been associated with increased cellular proliferation, including T-cells. Additionally, high leptin levels may stimulate the synthesis of proinflammatory cytokines such as ILـ6 and TNFـα.Objectives: To evaluate the effect of Apremilast on Leptin in obese psoriatic patients.Subjects and Methods: Thirty patients with psoriasis were included in This prospective cohort study to measure the levels of serum Leptin by using the ELISA technique, before and after receiving Apremilast.Result: The present work found the concentration of Leptin before receiving Apremilast was 2.365 ng/ml, and after six months from baseline, it was reduced to 1.933 ng/ml, which was statistically significant (P